2017
DOI: 10.1007/s40732-017-0219-2
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of U-Value as a Measure of Variability

Abstract: The variability in behavior has frequently been assessed using a measure known as the U-value. Of concern in the present paper were the limits and constraints on U-value as a measure of variability. The relation between the U-value and aspects of variability was examined using three sets of simulated data. Our analysis demonstrates that the U-value as a measure of variability on its own fails to capture repetitive patterns in the sequence of responding. The U-value was shown to reflect the evenness of the dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…The field of research concerned with behavioral variability is limited by the current analytic techniques (Kong et al, 2017). U-value is the measure most commonly used in behavioral variability studies (for reviews, see Neuringer, 2002Neuringer, , 2009Neuringer, , 2012Neuringer, , 2016.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The field of research concerned with behavioral variability is limited by the current analytic techniques (Kong et al, 2017). U-value is the measure most commonly used in behavioral variability studies (for reviews, see Neuringer, 2002Neuringer, , 2009Neuringer, , 2012Neuringer, , 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Higher U-values indicate higher levels of behavioral variability. Although U-value can be a useful molar measure of behavioral variability, it has limitations (Kong, McEwan, Bizo, & Foster, 2017;Neuringer et al, 2001). Namely, U-value is dependent on the number of sequences included in the calculation, that is, the number of trials completed in a session.…”
Section: Methodsmentioning
confidence: 99%
“…d , Rat paradigm: subjects choose between three noseports with different probabilities of sucrose pellet reward. e , Reward contingency schedule for rat experiment 39 .…”
Section: Resultsmentioning
confidence: 99%
“…3b; F (1)=9.207, P =0.003, η p 2 =0.030, MD=0.059, CI=[0.021, 0.097]; version trend: F (3)=2.263 P =0.081, η p 2 =0.022; low paranoia: m= 0.06 [0.01], high paranoia: m= 0.12 [0.02]). To elucidate whether this behaviour was stochastic or predictable (e.g., switching back to a previously rewarding option), we calculated U-values 39 , a metric of behavioural variability employed by behavioural ecologists (increasingly an inspiration for human behavioural analysis 40 ), particularly with regards to predator-prey relationships 41 . When a predator is approaching a prey animal, the prey’s best course of action is to behave randomly, or in a protean fashion, in order to evade capture 41 .…”
Section: Resultsmentioning
confidence: 99%
“…The simulations for each experiment were conducted in sequence and the random seed value was not changed across the analyses. Galizio et al (2018) reported results with data summarized across blocks of five sessions to account for the potential difficulty of calculating U-value as a measure of variability during extinction when only a few response sequences are emitted (Kong, McEwan, Bizo, & Foster, 2017). To make the results of this Monte Carlo simulation comparable to the results reported in Galizio et al (2018), we used the same data from five-session blocks.…”
Section: Monte Carlo Methodsmentioning
confidence: 99%